Novel low-temperature colorimetric indicator based on functional PDA/PVA - Sachin Goyal; Deepika Sharma; Amit L Sharma; Kamlesh Kumar (Chemical Physics Impact)
The conjugated polydiacetylene (PDA) polymers have garnered significant attention due to their potential use as a thermochromic indicator. The color transition at low-temperature ranges makes them suitable for monitoring frozen foods and medicinal products. This study presents the synthesis and characterization of a novel thermochromic molecule that experiences a low-temperature irreversible color transition. The synthesis of modified monomeric dye involves an esterification (Steglich) reaction between 10,12-Pentacosadiynoic acid (PCDA) and phenol. The formation of the ester moiety in the dye derivative was confirmed using FTIR and NMR spectroscopy. The composite film was fabricated by mixing modified monomer dye with the polymer polyvinyl alcohol (PVA), which, upon UV light exposure, undergoes topochemical polymerization, forming PDA via 1,4-addition reaction between the respective diacetylene monomeric units. Thermochromic studies of this dye showed a low-temperature irreversible color transition above 15 °C, contrasting the reversible color transition of pristine dye above 45 °C and characterized with absorption and Raman spectroscopy. Consequently, the results may uncover the potential applications of the conjugated PDA-based irreversible thermochromic dye as a warning indicator for frozen packaged food and pharmaceutical items.